EVALUATION OF THE BEARING CAPACITY VALUE OF SOFT CLAY SOIL DUE TO THE INFLUENCE OF BEACH SAND ADDITION - Saskia Malikha Putri; Revianty Nurmeyliandari; Ghina Amalia (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2026)
Land is categorized as suitable for use as embankment and subgrade based on the California Bearing Ratio (CBR) value. According to the Indonesian National Standard (SNI), the soil bearing capacity value requirement is categorized as good if the CBR value based on field testing is ≥3% and based on the laboratory the value is ≥6%. However, not all soil categories meet these requirements, for example soft clay soil. Soft soil layers have characteristics such as tending to be very compressible, low shear resistance, low permeability, and low bearing capacity. Efforts to increase the bearing capacity of the soil so that it can be used for construction are carried out by soil stabilization. This study aims to determine the increase in the bearing capacity value of soft clay soil with a mixture of beach sand with variations of 10.5%, 15%, and 20% and to determine the optimum content of beach sand that can increase the CBR value. The results of the study showed that the higher the percentage of beach sand, the higher the CBR value, the optimum content of beach sand is with the addition of 20% with a CBR value of 24.80% and is included in the category of very good material for base or subbase.